Genetic profiling and precision skin care: a review - Geusens, Barbara; Haykal, Diala (Frontiers in Genetics, 2025)
Skin aging is a multifaceted biological phenomenon driven by intrinsic and extrinsic factors, including genetics, hormonal changes, metabolic shifts, and environmental influences. Notably, genetic factors play a significant role, explaining up to 60% of the variability in how individuals age. Genes such as elastin (ELN), filaggrin (FLG), and melanocortin 1 receptor (MC1R) play pivotal roles in processes like elasticity, hydration, and pigmentation, directly impacting both intrinsic and extrinsic aging pathways. Understanding these genetic mechanisms is crucial for advancing personalized anti-aging products and therapies, particularly given the significant variability among individuals and ethnic groups. This review explores the current state of knowledge regarding the genetic determinants of skin aging, highlighting recent discoveries and proposing functional pathways for targeted interventions. Future directions are discussed to highlight the transformative potential of these innovations in clinical and aesthetic dermatology. While genetic factors may account for up to 60% of skin aging variability in specific populations, this figure should be interpreted with caution. It primarily reflects heritability under controlled conditions and does not negate the significant influence of modifiable lifestyle and environmental factors on skin and overall aging.